2020
DOI: 10.1177/0883073820972231
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pediatric Pseudotumor Cerebri Clinical Characteristics and Outcomes

Abstract: Pseudotumor cerebri also known as idiopathic intracranial hypertension is a relatively uncommon disorder of unknown pathophysiology. Although pseudotumor cerebri occurs in both children and adults, the pseudotumor cerebri literature is heavily dominated by adult studies. The aim of this study is to retrospectively describe the clinical presentation, imaging, treatment, and outcomes of a large pediatric pseudotumor cerebri population over a 23-year period. We also discuss secondary pseudotumor cerebri (44%) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 39 publications
(56 reference statements)
1
23
0
1
Order By: Relevance
“…Although to a lesser degree, Yamamoto et al also found that 22 patients (13.3%) in their study did not present with symptoms such as headache but were found to have papilledema on examination. 7 Furthermore, our study found asymptomatic females and children older than 12 years had a higher risk of positive findings on neuroimaging when compared to males and children under 12 years. This may suggest a lower threshold for neuroimaging should be emphasized in patients in certain demographic groups despite the lack of symptoms.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Although to a lesser degree, Yamamoto et al also found that 22 patients (13.3%) in their study did not present with symptoms such as headache but were found to have papilledema on examination. 7 Furthermore, our study found asymptomatic females and children older than 12 years had a higher risk of positive findings on neuroimaging when compared to males and children under 12 years. This may suggest a lower threshold for neuroimaging should be emphasized in patients in certain demographic groups despite the lack of symptoms.…”
Section: Discussionmentioning
confidence: 49%
“…When symptoms were reported, headache was most commonly reported followed by visual disturbances, consistent with prior studies. 4 , 5 , 7 However, 56 children in our study were asymptomatic at presentation. Despite the lack of symptoms, 41% of asymptomatic patients were diagnosed with papilledema.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In our case, the neurosurgeon described the opening pressure as increased on both occasions by counting the number of CSF drops flowing through the spinal needle in a specified period, as already described [ 6 , 7 ], however we do not know the precise pressure measurement. In published studies on PTCS, CSF opening pressure was not documented for all the patients, because other factors documented indirectly elevated CSF pressure (symptoms, imaging data) [ 8 , 19 ]. Our infant presented with papilloedema and bulging anterior fontanel, which represent indirect signs of high CSF pressure.…”
Section: Discussionmentioning
confidence: 99%
“…IIH is a syndrome of increased intracranial pressure with normal cerebrospinal fluid composition, normal neuroanatomy, absence of space-occupying mass, and a normal neurological examination [4]. The term PTCS has been used to incorporate both primary and secondary causes as the term IIH cannot be used for patients having clinical features with an identifiable etiology [5].…”
Section: Discussionmentioning
confidence: 99%